Bioethical aspects in the final stage of life - Lascano Sánchez , Adriana del Rocío (2022)
Introduction: The bioethical aspects describe the importance of beneficence, non-maleficence, autonomy and justice in order to provide both physical and spiritual well-being that should be granted to a patient in his final stage of life. Objective: To describe the bioethical aspects in the final stage of life, the same one that is carried out through a systematic review of the bibliography. Methodology: 30 articles were reviewed in databases such as: Medline, Google Scholar, Scielo, Scopus, Science Citation Inde, web of science through descriptions such as bioethical principles at the end of life. Results: Bioethics influences decision-making through appropriate reflections of each situation, plays an important role in professional practice, since autonomy is the ability of each person to make their own decisions about their treatment, recovery and be responsible. from the same. Conclusions: The bioethical aspects are of importance, proving to be a correct practice, because it provides quality care and warmth to the patient, granting efficient care related to the emotional state, granting a dignified death and in this way the nursing staff plays an important role in Provide palliative care to help with your pain.